2023
DOI: 10.18472/sustdeb.v14n1.2023.44277
|View full text |Cite
|
Sign up to set email alerts
|

The active dismantling of environmental policy in Brazil: paralysis and setbacks of the deforestation inspection and control

Abstract: The paper aims to analyse the street-level bureaucrats’ (SLBs) perception of President Bolsonaro’s administration’s effects on Brazilian environmental policy, emphasising deforestation prevention and control in the Legal Amazon1. Besides the policy dismantling concepts, a theoretical model integrating three complementary analytical dimensions of SLBs’ action – institutional, individual, and relational – was employed in a case-oriented investigation of environmental bureaucrats – Ibama Inspectors and ICMBio Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…Regarding the type of dismantling strategy adopted, since mid-2010, by the federal government, most of the interviewees agreed that the prevailing is active (Bauer & Knill, 2013), i.e., marked by high visibility and clear preference to dismantle, which is also in line with the research of Bonelli et al (2023) and Gomide et al (2023). However, the policymakers' willingness to undertake the process differs among the Administrations, as Interviewee 6 supported: "Dilma and Temer cut, but they tried believing. "…”
Section: Dismantling Featuressupporting
confidence: 77%
See 1 more Smart Citation
“…Regarding the type of dismantling strategy adopted, since mid-2010, by the federal government, most of the interviewees agreed that the prevailing is active (Bauer & Knill, 2013), i.e., marked by high visibility and clear preference to dismantle, which is also in line with the research of Bonelli et al (2023) and Gomide et al (2023). However, the policymakers' willingness to undertake the process differs among the Administrations, as Interviewee 6 supported: "Dilma and Temer cut, but they tried believing. "…”
Section: Dismantling Featuressupporting
confidence: 77%
“…In this particular area, Direito et al (2022), analyzing the Single Registry for Social Programs (Cadastro Único), identified dismantling signs since 2019, despite uncertainties and growing demand for social protection. Finally, Bonelli et al (2023) address the phenomenon in the environmental policy in the Legal Amazon and demonstrate that an active dismantling process has been ongoing since the beginning of Bolsonaro's administration, provoking paralysis and setbacks in deforestation inspection and control policies and posing severe risks to the environmental protection in the country. Understanding how the opposition to dismantling behaves is equally relevant, considering they can avoid, postpone, or reduce drastic policy changes, such as program termination or complete budgeting cuts.…”
Section: Imentioning
confidence: 99%
“…Nessa área específica, Direito et al (2022), analisando o Cadastro Único para Programas Sociais (Cadastro Único), identificaram sinais de desmantelamento desde 2019, apesar das incertezas e da crescente demanda por proteção social. Por fim, Bonelli et al (2023) abordam o fenômeno na política ambiental na Amazônia Legal e demonstram que um ativo processo de desmonte estava em curso desde o início do governo Bolsonaro, provocando paralisias e retrocessos nas políticas de fiscalização e controle do desmatamento e representando graves riscos à proteção ambiental do país.…”
Section: Explicação Do Desmantelamento De Políticas: Um Modelo Analíticounclassified